2013
DOI: 10.5152/ucd.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Wound surveillance with ASEPSIS in colorectal surgery

Abstract: Kolorektal cerrahi geçiren hastalar Yara yeri enfeksiyonları (YYE) açısından yüksek riske sahiptir (1,2). Yara yeri komplikasyonlarının yakından izlemi yara iyileşmesi ve hasta sağ kalımı üzerinde olumlu etki yapmaktadır (3-8). Bu çalışmadaki amaçlar kolorektal cerrahide YYE gelişmesine neden olan faktörleri araştırmak, YYE şiddetini ve iyileşme sürecini yara skorlama yöntemi olan ASEPSIS ile izlemek ve YYE riskini belirlemek amacıyla kullanılan NNIS (National Nosocomial Infections Surveillance System) ve SENI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…[3] As a result of resuscitation with 5% albumin, cardiac output has been reported to reach pre-injury values in 6 hours. [19] Aktaş et al [20] showed that the preoperative albumin levels were associated with wound infection in patients undergoing colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[3] As a result of resuscitation with 5% albumin, cardiac output has been reported to reach pre-injury values in 6 hours. [19] Aktaş et al [20] showed that the preoperative albumin levels were associated with wound infection in patients undergoing colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%